Disruption of Endocytosis with the Dynamin Mutant shibire[ts1] Suppresses Seizures in Drosophila. - Kroll, J.R.; Wong, K.G.; Siddiqui, F.M.; Tanouye, M.A. (Genetics, 2015)
One challenge in modern medicine is to control epilepsies that do not respond to currently available medications. Since seizures consist of coordinated and high-frequency neural activity, our goal was to disrupt neurotransmission with a synaptic transmission mutant and evaluate its ability to suppress seizures. We found that the mutant shibire, encoding dynamin, suppresses seizure-like activity in multiple seizure-sensitive Drosophila genotypes, one of which resembles human intractable epilepsy in several aspects. Because of the requirement of dynamin in endocytosis, increased temperature in the shi(ts1) mutant causes impairment of synaptic vesicle recycling and is associated with suppression of the seizure-like activity. Additionally, we identified the giant fiber neuron as critical in the seizure circuit and sufficient to suppress seizures. Overall, our results implicate mutant dynamin as an effective seizure suppressor, suggesting that targeting or limiting the availability of synaptic vesicles could be an effective and general method of controlling epilepsy disorders.